Airway abnormalities in very early treated infantile‐onset Pompe disease: A large‐scale survey by flexible bronchoscopy - Yang, Chia‐Feng; Niu, Dau‐Ming; Tai, Shyh‐Kuan; Wang, Ting‐Hao; Su, Hsiao‐Ting; Huang, Ling‐Yi; Soong, Wen‐Jue (American journal of medical genetics. Part A, 2020)
Early enzyme replacement therapy (ERT) improve long‐term outcomes in patients with infantile‐onset Pompe disease (IOPD). Our cohort of patients with IOPD at Taipei Veterans General Hospital (TVGH) joined Taiwan Pompe newborn screening program from 2008, testing more than one million newborns until 2018. By 2010, we had established rapid diagnostic strategies. Now, the average age of ERT initiation starts at an average age of <10 days‐old, the earliest group in the world. However, they still presented some airway problems. We present a retrospective study focused on airway abnormalities in these patients along 8 years of observation. Fifteen patients with IOPD, who received very early treatment at a mean age of 8.94 ± 3.75 days, underwent flexible bronchoscopy (FB) for dynamic assessment of the whole airway. Long‐term clinical outcomes and relevant symptoms of the upper airway were assessed. All patients in the study had varying degrees of severity of upper airway abnormalities and speech disorders. The three oldest children (Age 94, 93, and 88 months, respectively) had poor movement of the vocal cords with reduced abduction and adduction and had silent aspiration of saliva through the glottis during respiration. This is the largest cohort study presented to date about airway abnormalities in very early treated patients with IOPD patients by FB. Despite very early treatment, we observed upper airway abnormalities in these IOPD patients. In IOPD, upper airway abnormalities seem inevitable over time. We suggest early and continuous monitoring for all IOPD patients, even with early and regular treatment.